2014
DOI: 10.1246/cl.140020
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reduction of Cr(VI) under Visible Light over Bi2WO6 with Different Morphologies

Abstract: Bi2WO6 samples with different morphologies were hydrothermally synthesized and applied to the photoreduction of hexavalent chromium under visible-light irradiation. It was found that nanosheets with high exposure of {100} facets and crystallinity exhibited the best photocatalytic performance: two times as active as nanoparticles based on specific rate constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The synthesized Bi 2 WO 6 and Bi 2 S 3 /Bi 2 WO 6 composites with hierarchical heterostructures were used as photocatalysts for a reduction of Cr (VI) ions. Deng et al previously reported high reduction efficiency for Cr­(VI) using Bi 2 WO 6 with different morphologies by irradiating LED white light rather than using simulated solar light Figure shows the photoreduction efficiencies of Cr­(VI) in the presence of different catalysts after exposure to visible light for 60 min at room temperature and ambient pressure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesized Bi 2 WO 6 and Bi 2 S 3 /Bi 2 WO 6 composites with hierarchical heterostructures were used as photocatalysts for a reduction of Cr (VI) ions. Deng et al previously reported high reduction efficiency for Cr­(VI) using Bi 2 WO 6 with different morphologies by irradiating LED white light rather than using simulated solar light Figure shows the photoreduction efficiencies of Cr­(VI) in the presence of different catalysts after exposure to visible light for 60 min at room temperature and ambient pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Deng et al previously reported high reduction efficiency for Cr(VI) using Bi 2 WO 6 with different morphologies by irradiating LED white light rather than using simulated solar light. 11 Figure 7 shows the photoreduction efficiencies of Cr(VI) in the presence of different catalysts after exposure to visible light for 60 min at room temperature and ambient pressure. For comparison, photocatalytic experiments were also performed with no catalyst, nonporous and cubic structured Bi 2 S 3 /Bi 2 WO 6 and P25 of TiO 2 as reference photocatalysts.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all of these, photocatalytic removal of Cr­(VI) by semiconductor photocatalysts is considered as an attractive and gainful method. In the photocatalytic reduction process, Cr­(VI) is reduced to Cr­(III) which is nontoxic and plays a vital role in plant and animal metabolism. , Therefore, semiconductor photocatalysts such as TiO 2 , ZnO, SnS 2 , ZnGeO 4 , Sn 2 S 3 , and Bi 2 WO 6 have been reported for the reduction of Cr­(VI) to Cr­(III). …”
Section: Introductionmentioning
confidence: 99%